Criminal Responsibility of ISIS for the Religious Identity Change of Yazidi Children and Mechanisms of Reparations: A Study in Light of Iraqi Law - Al-Akili, Ali (Journal of Legal Sciences, 2026)
Preliminary Opinion: The crime of altering the religious identity of Yazidi children constitutes one of the most serious manifestations of collective human rights violations, as it transcends the limits of individual assault to strike at the very core of an entire community, targeting its religious and cultural identity. From a legal perspective, these acts represent a deeply rooted threat to the essence of the human community and its right to exist, elevating them to the level of genocide under international law, in accordance with the provisions of the 1948 Convention on the Prevention and Punishment of the Crime of Genocide and the Statute of the International Criminal Court.At the national level, Iraqi criminal law affirms that such acts fall within the scope of genocide, holding perpetrators criminally responsible, whether they are individuals or organizations. It has been further argued that classifying the crime of altering religious identity as a criminal offense—considering freedom of religion as a constitutionally and legally protected right—is not merely a legal obligation, but an urgent necessity recognized in all divine and positive legal systems. However, criminal justice is not fulfilled by punishment alone; it also requires effective mechanisms for reparation, including the restoration of the children’s religious identity, the provision of psychological and social care, as well as material and moral compensation